UCAT: the Unified Codio Autograding Tool - Bland, Joel G. (Kansas State University, 2023)
To meet increasing enrollment demands in computer science courses, many institutions employ automated coursework assessment tools. In this report, we present such a tool titled UCAT: The Unified Codio Autograding Tool. Codio is a web service for administering programming homework assignments with only limited grading capabilities. UCAT expands these capabilities using unit-test-based assessment for partial credit, a feedback pipeline from instructor to student, automatic static code analysis, and more. UCAT is designed to be platform-independent, unifying assessment efforts across different programming languages into one tool.
Keywords: Autograders; Computer science education; Automated assessment